Islanding operation of hybrid microgrids with high integration of wind driven cage induction generators - Ambia, M.; Al-Durra, A.; Caruana, C.; Muyeen, S.M. (2016)
This paper proposes two control strategies for the islanding operation of hybrid microgrid with a high penetration of wind driven cage induction generators. The control strategies combine approaches traditionally applied to self-excited cage induction generators with recent approaches for microgrid's islanding operation. The proposed control strategies aim to facilitate the higher integration of cage induction generators in microgrids. The first strategy is based on direct frequency and reactive power control while the second one uses an artificial grid to regulate the voltage amplitude and frequency. The proposed schemes are tested in PSCAD/EMTDC using a real wind speed pattern measured at Hokkaido Island of Japan. Simulation results show the successful operation of both schemes. The implementation simplicity and cost-effectiveness of both schemes are explained as well.